The Effect of Using Video Blogging towards Students’ Speaking Ability in Vocational School (RETAIN, 2020)
This research is aimed to find out the effect of using video blogging towards students’ speaking ability in vocational school. The researcher is using quasi-experimental design with SPSS 25 which the result is described in the form of number and interpreted in the form of word. In this research, there are 2 classes that going to be investigated, experimental class and control class. Based on the result of this research, the effect size of the use of video blogging towards students’ speaking ability that was calculated by using Cohen’s d is weak effect. It can be concluded that students who taught speaking by using video blogging do not achieved better score than students who taught by using expository way in the class. Key works: Speaking, Video Blogging, Students’ Ability